Digital Marketing Strategies for Enhancing Brand Awareness: A Case Study of Hola Koffie in Bandung City - Camelia Rizki Agrina; Adnan Prasetyo; Alisha Rahma Alfiyah (International Journal of Management and Business Economics, 2025)
The intense competition in the coffee shop industry in Bandung requires business owners to develop effective marketing strategies. This study aims to analyze and design a digital marketing strategy to increase brand awareness for Hola Koffie, a coffee shop targeting young consumers with affordable prices and premium quality. The approach includes designing brand guidelines, implementing content marketing, advertising campaigns, and offline activations through Instagram, TikTok, and GrabFood over a four-month period. The results show that consistent implementation of digital marketing strategies can increase reach and engagement on social media, as well as support revenue growth. This study emphasizes the importance of integrating digital and conventional marketing to create effective communication and build emotional connections with customers.